Analysis of rainfall pattern and extreme events during southwest monsoon season over Varanasi during 1971-2010 - BHATLA, R.; TRIPATHI , A.; SINGH, R. S. (MAUSAM, 2016)
An attempt has been made to detect the pattern of rainfall and examine the trends and variations of extreme events of rainfall over Varanasi (Uttar Pradesh, India) through seasonal, monthly and decadal analysis during southwest monsoon season (June-September) using the daily rainfall data of 40 years period from 1971-2010. The results show that cumulative rainfall during 1971-2010 is overall decreasing in monsoon season as well as in all the months June, July, August and September. In general, the observed rainfall events in all categories (Non rainy day, 0-2.4 mm; Category I, 2.5-64.4; Category II, 64.5 to 124.4; Category III, 124.5 mm or more) have a decreasing trend in all the months and monsoon season over the entire period of study. However, decadal analysis reveals that in general frequency of rainfall events in almost every category is decreasing in recent decade. Different results are seen in August, as cumulative rainfall is decreasing in this month, whereas very heavy and exceptionally heavy rainfall events and their contribution have increased in recent decade as well as over total period.